Commercialization of Non-timber Forest Products in Ghana: Processing, Packaging and Marketing - Ahenkan, A.; Boon, E. (My University, 2010)
The collection and marketing of Non-timber Forest Products (NTFPs) in Ghana are being promoted as a potential solution to the current high rates of malnutrition, the poor health of the rural population and the spread and intensification of poverty. Accomplishing these goals requires an understanding of how NTFPs are extracted, processed and marketed in rural areas. It is an important means for economic growth and sustainable forest management in local communities. Despite the potential of NTFPs in poverty reduction and livelihoods improvement in rural areas in Ghana, little is known about their collection, procession, packaging and labeling. This paper examines the supply chain and commercialization of NTFPs in rural settings in Ghana and their potential to contribute to poverty reduction, food security and livelihoods improvement. The study uses an exploratory and qualitative research methodology, including an extensive literature review, consultations with key informants, administration of questionnaires, interviews and stakeholder consultations. The results of the study indicated that NTFPs contribute significantly to the food security, poverty reduction and livelihoods development in Ghana. The marketing of these products, however, faces a number of critical processing, labeling and marketing challenges. The NTFPs marketing often occurs in an informal way, resulting in uncertainty about prices and yields. Marketing is basically done individually; it is unorganized, dispersed and farmers lack the necessary marketing skills and information required for optimal performance. Promoting the development and commercialization of these products on a permanent basis will enormously help to create more sustainable employment and income-generation opportunities, enhance food security and improve the livelihoods of farmers, their families and communities. The paper also identifies and analyses a number of critical factors that hinder the commercialization of NTFPs in Ghana and recommends strategies for redressing them.
Keywords: Commercialization; food security; livelihood improvement; labeling; marketing; nutrition; non-timber forest products; packaging; poverty reduction; processing